HDAC6 and USP9X Control Glutamine Metabolism by Stabilizing GS to Promote Glioblastoma Tumorigenesis - Go Woon Kim; Minhae Cha; Hien Thi My Ong; Jung Yoo; Yu Hyun Jeon; Sang Wu Lee; Soo Yeon Oh; Min‐Jung Kang; Youngsoo Kim; So Hee Kwon (Advanced Science, 2025)
Abstract Glioblastoma (GBM) is the most common and the deadliest brain cancer. Glutamine anabolism mediated by glutamine synthetase (GS) is beneficial for GBM cell growth, especially under glutamine deprivation. However, the molecular mechanism underlying GS homeostasis in GBM remains undisclosed. Here, it is reported that histone deacetylase 6 (HDAC6) promotes GS deacetylation, stabilizing it via ubiquitin‐mediated pathway. It is found that deubiquitination of GS is modulated by ubiquitin‐specific peptidase 9, X‐linked (USP9X). USP9X stabilizes GS by removing its K48‐linked polyubiquitination on lysine 91 and 103. Accordingly, targeting HDAC6 and USP9X in vitro and in vivo represses GBM tumorigenesis by decreasing GS stability. Metabolic analysis shows that silencing HDAC6 and USP9X disrupts de novo nucleotide synthesis, thereby attenuating GBM cell growth. Furthermore, GS modulation by targeting HDAC6 and USP9X restrains the self‐renewal capacity. These results suggest that HDAC6 and USP9X are crucial epigenetic enzymes that promote GBM tumorigenesis by modulating glutamine metabolism.